Efektivitas Layanan Informasi Berbasis Video Animasi untuk Meningkatkan Sikap Toleransi Siswa di Sekolah Berbasis Asrama - Putra, Roby Maiva; Ajid, Ajid (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2024)
The attitude of tolerance is essential for students in boarding schools to create a positive atmosphere within the school environment. Additionally, it is crucial for preparing students to face challenges in society. The aim of this research is to determine the effectiveness of animation-based video information services in enhancing students' tolerance in boarding schools. This study employs a quantitative approach with a one-group pretest-posttest design. The implementation of the animation-based video information service is conducted in a classical format. The population of the study consists of 321 students from Madrasah Aliyah Negeri Insan Cendekia (MAN IC) in Batam City, from which a sample of 25 students is taken using purposive sampling techniques. The experimental research was conducted over four meetings according to the schedule. Hypothesis testing in this study used the paired sample t-test formula. The findings indicate that the Sig. (2-tailed) value in the output Pair 1 is 0.000 < 0.05, thus concluding that Ho is rejected and Ha is accepted, meaning that the animation-based video information service is effective in improving students' tolerance in boarding schools.